2010
DOI: 10.1002/ajmg.a.33656
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic deletions of IL1RAPL1: Report of two cases and review of the literature

Abstract: IL1RAPL1 (interleukin-1 receptor accessory protein-like 1) located at Xp21.3-22.1 has repeatedly been shown to be deleted in patients with a contiguous gene syndrome also affecting neighboring genes, in particular DMD (dystrophin), DAX-1 (NR0B1, nuclear receptor subfamily 0, group B, member 1), and GK (glycerol kinase). In contrast, intragenic deletions of IL1RAPL1 or other mutations or cytogenetic aberrations affecting IL1RAPL1 have only rarely been identified. Up to date, they have mostly been associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…We propose that small 10 bp deletion may have created a sequence conformation favouring further instability and leading to the larger deletion observed in the second brother (see online supplementary figure S14). Indeed, a large proportion of IL1RAPL1 causative mutations are intragenic exon deletions or pericentric inversions,19 supporting that IL1RAPL1 region is highly susceptible to recombination events.…”
Section: Resultsmentioning
confidence: 95%
“…We propose that small 10 bp deletion may have created a sequence conformation favouring further instability and leading to the larger deletion observed in the second brother (see online supplementary figure S14). Indeed, a large proportion of IL1RAPL1 causative mutations are intragenic exon deletions or pericentric inversions,19 supporting that IL1RAPL1 region is highly susceptible to recombination events.…”
Section: Resultsmentioning
confidence: 95%
“…Accumulating evidence supports the importance of synaptic adhesion proteins in ID. For example, researchers have found multiple mutations in IL1RAPL1 (interleukin-1 receptor accessory protein-like 1) in ID and ASD patients (Behnecke et al 2011 with postsynaptic partners PSD95 and Rho-GAP to cooperatively regulate glutamatergic synapse number, synaptic transmission, plasticity, and cognitive function (Pavlowsky et al 2010, Yasumura et al 2014. Neuroligins (NLGNs) are another class of postsynaptic cell adhesion molecules that regulate synapse maturation and stabilization in cooperation with their presynaptic partner neurexins (NRXNs).…”
Section: Intellectual Disabilitymentioning
confidence: 99%
“…In addition to point mutations and indels [38,39], exome sequencing data can be used to discover larger events of potential relevance to disease [40,41]. Similarly, higher resolution and targeted array studies have identified numerous candidate CNVs well below 500 kbp [42][43][44][45][46]. Some recent prominent examples include a small duplication of VIPR2 in schizophrenia, and focal partial deletions of TMHLE in ASD [44,47,48].…”
Section: Size Spectrum Of Copy Number Variationmentioning
confidence: 99%